A Novel Magnetic Hardening Mechanism for Nd‐Fe‐B Permanent Magnets Based on Solid‐State Phase Transformation. (27th November 2022) - Schäfer, Lukas; Skokov, Konstantin; Maccari, Fernando; Radulov, Iliya; Koch, David; Mazilkin, Andrey; Adabifiroozjaei, Esmaeil; Molina‐Luna, Leopoldo; Gutfleisch, Oliver
Abstract: Permanent magnets based on neodymium‐iron‐boron (Nd‐Fe‐B) alloys provide the highest performance and energy density, finding usage in many high‐tech applications. Their magnetic performance relies on the intrinsic properties of the hard‐magnetic Nd2 Fe14 B phase combined with control over the microstructure during production. In this study, a novel magnetic hardening mechanism is described in such materials based on a solid‐state phase transformation. Using modified Nd‐Fe‐B alloys of the type Nd16 Febal‐x‐y‐z Cox Moy Cuz B7 for the first time it is revealed how the microstructural transformation from the metastable Nd2 Fe17 Bx phase to the hard‐magnetic Nd2 Fe14 B phase can be thermally controlled, leading to an astonishing increase in coercivity from ≈200 kAm −1 to almost 700 kAm −1 . Furthermore, after thermally treating a quenched sample of Nd16 Fe56 Co20 Mo2 Cu2 B7, the presence of Mo leads to the formation of fine FeMo2 B2 precipitates, in the range from micrometers down to a few nanometers. These precipitates are responsible for the refinement of the Nd2 Fe14 B grains and so for the high coercivity. This mechanism can be incorporated into existing manufacturing processes and can prove to be applicable to novel fabrication routes for Nd‐Fe‐B magnets, such as additive manufacturing. Abstract : A novel magnetic hardening mechanism in neodymium‐iron‐boron (Nd‐Fe‐B) alloys based on the formation of a metastable Nd2 (Fe, Co)17 Bx phase and subsequent microstructural transformation by heat treatment is observed. The addition of cobalt, molybdenum, and copper leads to an increase in coercivity due to optimization of the parent microstructure and grain refinement.